2017
DOI: 10.1099/ijsem.0.002415
|View full text |Cite
|
Sign up to set email alerts
|

List of new names and new combinations previously effectively, but not validly, published

Abstract: List of new names and new combinations previously effectively, but not validly, published

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…6,9,12,40 Nevertheless, recent whole genome sequence data followed by maximum-likelihood phylogeny using 106 concatenated orthologous genes 10 provided strong support for separating Burkholderia sensu lato into Burkholderia sensu stricto, Paraburkholderia, Caballeronia, and Robbsia. 12,13,[41][42][43] Further phylogenomic analyses supported inclusion of the fungal endosymbionts Paraburkholderia rhizoxinica (basonym Burkholderia rhizoxinica) and Paraburkholderia endofungorum (basonym Burkholderia endofungorum) in the recently proposed genus Mycetohabitans. 44 In addition, the new genus Trinickia was also proposed, including the nodulating Paraburkholderia symbiotica, the plant pathogen Paraburkholderia caryophylli, and the soil bacterium Paraburkholderia soli.…”
Section: Taxonomy and Ecological Diversity Of Burkholderia Bacteriamentioning
confidence: 98%
See 1 more Smart Citation
“…6,9,12,40 Nevertheless, recent whole genome sequence data followed by maximum-likelihood phylogeny using 106 concatenated orthologous genes 10 provided strong support for separating Burkholderia sensu lato into Burkholderia sensu stricto, Paraburkholderia, Caballeronia, and Robbsia. 12,13,[41][42][43] Further phylogenomic analyses supported inclusion of the fungal endosymbionts Paraburkholderia rhizoxinica (basonym Burkholderia rhizoxinica) and Paraburkholderia endofungorum (basonym Burkholderia endofungorum) in the recently proposed genus Mycetohabitans. 44 In addition, the new genus Trinickia was also proposed, including the nodulating Paraburkholderia symbiotica, the plant pathogen Paraburkholderia caryophylli, and the soil bacterium Paraburkholderia soli.…”
Section: Taxonomy and Ecological Diversity Of Burkholderia Bacteriamentioning
confidence: 98%
“…Burkholderia included >100 species as of 2015, representing a large, heterogeneous, and taxonomically controversial group of bacteria. ,, In fact, phylogenetic analyses performed by different research groups indicated that Burkholderia is polyphyletic. , Due to this heterogeneity, a split of the genus Burkholderia was proposed. ,, However, 16S rRNA phylogenetic trees or even conventional multilocus sequence analysis using a small number of genes initially provided limited support for the new lineages within Burkholderia . ,,, Nevertheless, recent whole genome sequence data followed by maximum-likelihood phylogeny using 106 concatenated orthologous genes provided strong support for separating Burkholderia sensu lato into Burkholderia sensu stricto, Paraburkholderia , Caballeronia , and Robbsia . ,,− Further phylogenomic analyses supported inclusion of the fungal endosymbionts Paraburkholderia rhizoxinica (basonym Burkholderia rhizoxinica ) and Paraburkholderia endofungorum (basonym Burkholderia endofungorum ) in the recently proposed genus Mycetohabitans . In addition, the new genus Trinickia was also proposed, including the nodulating Paraburkholderia symbiotica , the plant pathogen Paraburkholderia caryophylli , and the soil bacterium Paraburkholderia soli …”
Section: Taxonomy and Ecological Diversity Of Burkholderia Bacteriamentioning
confidence: 99%